plataforma cloud computing como infraestructura tecnológica para laboratorios virtuales, remotos y adaptativos - Santamaría-Buitrago, Frey Alfonso; Ballesteros-Ricaurte, Javier Antonio; González-Sanabria, Juan Sebastián (Revista Científica, 2015)
Nowadays, institutions of higher education are developing teaching process leaning on virtual campus, in classroom and blended learning; as well as the internationalization of teaching creates new challenges, such as: creating research networks, shared workspaces, virtual and remote labs, among others; betting on production, publication and distribution systems of educative digital contents that allow sharing knowledge and educational material. This proposal pretends to potentiate the development of open, reusable and interoperable academic experimentation ecosystems, through the design of a framework and the technological integration oriented to the implementation of virtual and teleoperated labs, based on IMS Learning Tools Interoperability ® (LTI®) standard. This coupled with the characterization of a set of methods and technologies applicable to the development of virtual and teleoperated labs, identifying its scope and technical criteria, in order to offer informatics services in academic environments through the Internet and allowing a high scalability and flexibility in modifying the sizing of the service, academic and scientific research, supported on open standards, architectures, technologies, tools and apps.